Assessing correlation between different temporary restorative materials for microleakage following endodontic treatment: an in-vitro study - Qamar Hashem; Mohammed Mustafa; Mohammed A.S. Abuelqomsan; Ahmed Altuwalah; Ahmed A. Almokhatieb; Mohammad Fareed; Mohmed Isaqali Karobari (BMC Oral Health)
Abstract Background Coronal microleakage, the passage of fluids and bacteria through the interface between the temporary restoration and the tooth structure, can potentially result in endodontic treatment failure. Purpose This study evaluated and compared the sealing efficacy of various temporary restorative materials utilized during endodontic procedures. Methods All seventy premolar teeth were extracted, measured, and restored, except for the negative control group, where the teeth were left whole. There were eight distinct groupings created from the teeth. Sound teeth were utilized in the n = 5 (Group 1) negative control group. A cavity after endodontic treatment was left vacant in the positive control group (n = 5, Group 2). Six experimental groups, each with ten specimens, had access cavities restored using various temporary materials (Group 3: Cavit-W, Group 4: Systemp. inlay, Group 5: Cotton + Systemp. inlay, Group 6: Cotton + Cavit-W, Group 7: Teflon + Systemp. inlay and Group 8: Teflon + Cavit-W). The teeth were submitted to thermocycling, and a microleakage test was performed. Depth of dye penetration was measured. The collected data were statistically analyzed (α = 0.05). Results Gp 7: Teflon + Systemp. inlay obtained the lowest infiltration values with no significant difference than (Gp 4: Systemp.inlay) and (Gp 8: Teflon + Cavit-W). Whereas (Gp 5: Cotton + Systemp.inlay) and (Gp 6: Cotton + Cavit-W) presented the highest significant microleakage values among other experimental groups. Conclusion Regarding temporization after endodontic treatment, Teflon combined with Systemp.inlay and Cavit-W presented the best temporary materials regarding microleakage control. At the same time, cotton combined with Cavit-W presented the worst temporary material for microleakage control. Cotton is not to be used in the temporization of endodontic-treated teeth. Clinical implication Creating a tight seal in root canals that have undergone endodontic treatment is crucial for a successful, durable final restoration. Clinical and laboratory research results are an essential factor in determining how well endodontic materials seal.